The environmental awareness character of elementary school students in the Kahayan River basin: Comparative study in rural and urban areas - Sunarno, Ali; Suryadi, Suryadi; Karliani, Eli; Sangalang, Ronald Hadibowo (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
This study compares the environmental awareness character of elementary school students in the Kahayan River Basin, Central Kalimantan Province, who live in rural and urban areas. It is a quantitative study using survey data collection methods. The survey was conducted on 60 students: 30 students from SDN Bukit Rawi 1, located in a rural area, and 30 students from SDN Percobaan Palangka Raya, in an urban area. The survey used a questionnaire containing 20 statements with five answer options, using a Likert scale. The collected data is then analyzed using descriptive percentage analysis. The results showed that students living in rural areas of the Kahayan River Basin had better environmental awareness than those living in urban areas. The majority, 70 percent of rural students, demonstrated "Very Good" ecological awareness, while the majority, 73 percent, of urban students, showed "Good" environmental awareness (one level below "Very Good"). Furthermore, rural students had an average score of 90.59 (Very Good), compared to urban students with an average score of 84.30 (Good). The researchers suggest further studies on the factors influencing students' environmental awareness and the development of products/programs to enhance environmental awareness among students in the Kahayan River Basin.